2018
DOI: 10.1002/mc.22781
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene RNA helicase DDX6 promotes the process of c‐Myc expression in gastric cancer cells

Abstract: Human DEAD-box RNA helicase gene DDX6 was cloned from B-cell lymphoma cell line RC-K8. Previously, we reported that DDX6 acts as oncogene in several cancers such as colorectal cancer and hepatocellular carcinoma. However, the detailed mechanism of DDX6 action in carcinogenesis is largely unknown. In this study, we examined the functions of DDX6 in clinical gastric cancer (GC) samples and GC cells. DDX6 protein expression levels of cancer samples were higher than those of the adjacent normal tissues in 25 clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
(85 reference statements)
0
26
0
Order By: Relevance
“…DDX46 is a member of the DDX RNA helicase family with ATP-dependent RNA helicase, that is located on chromosome 5q31.1 and plays a critical role in transcript splicing and ribosome assembly ( 20 ). Previous studies ( 21 23 ) in zebrafish have shown that DDX46 is required in the multilineage differentiation of hematopoietic stem cells and in the development of digestive organs and the brain.…”
Section: Discussionmentioning
confidence: 99%
“…DDX46 is a member of the DDX RNA helicase family with ATP-dependent RNA helicase, that is located on chromosome 5q31.1 and plays a critical role in transcript splicing and ribosome assembly ( 20 ). Previous studies ( 21 23 ) in zebrafish have shown that DDX46 is required in the multilineage differentiation of hematopoietic stem cells and in the development of digestive organs and the brain.…”
Section: Discussionmentioning
confidence: 99%
“…DDX6 binds to the 5′UTR of its target mRNA and recruits ribosomes, resulting in the initiation of translation (Supplementary Figure S5). In our previous studies, we detected the overexpression of DDX6 in most of the tumor samples and cell lines examined, and found that DDX6 positively regulates c-Myc expression at the translational step in various cancers [22,23,24]. Furthermore, DDX6 also positively regulates HER2 expression at the translation step in GC cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that oncogenic RNA helicase DDX6 was highly overexpressed in most of the malignant cell lines and clinical colorectal tumors that we had tested [ 7 , 8 ]. We also showed that DDX6 expression is linked to the regulation of translation of c-myc mRNA through the internal ribosome entry site (IRES) [ 9 ]. In addition, the DDX6 protein is most likely to interact with the 5-cap-structure binding protein eIF4E [ 6 , 10 ], which is a rate-limiting factor serving as a translation regulator for initiating translation.…”
Section: Discussionmentioning
confidence: 99%